Comprehensive analysis of miRNAs, lncRNAs, and mRNAs reveals potential players of sexually dimorphic and left-right asymmetry in chicken gonad during gonadal differentiation - Zou, X. (Poult Sci, 2020)
Despite thousands of sex-biased genes being found in chickens, the genetic control of sexually dimorphic and left-right asymmetry during gonadal differentiation is not yet completely understood. This study aimed to identify microRNAs (miRNAs), long noncoding RNAs (lncRNAs), messenger RNAs (mRNAs), and signaling pathways during gonadal differentiation in chick embryos (day 6/stage 29). The left and right gonads were collected for RNA sequencing. Sex-biased, side-biased miRNAs, lncRNAs, mRNAs, and shared differentially expressed miRNAs (DEmiRNA)–differentially expressed mRNAs (DEmRNA)–differentially expressed lncRNAs (DElncRNA) interaction networks were performed. A total of 8 DEmiRNAs, 183 DElncRNAs, and 123 DEmRNAs were identified for the sex-biased genes, and 7 DEmiRNAs, 189 DElncRNAs, and 183 DEmRNAs for the side-biased genes. The results of quantitative real-time PCR were generally consistent with the RNA-sequencing results. The study suggested that miRNAs and lncRNAs regulation were novel gene-specific dosage compensation mechanism and they could contribute to left-right asymmetry of chicken, but sex-biased and side-biased miRNAs, lncRNAs, and mRNAs were independent of each other. The competing endogenous RNA (ceRNA) networks showed that 17 target pairs including miR-7b (CYP19A1, FSHR, GREB1, STK31, CORIN, and TDRD9), miR-211 (FSHR, GREB1, STK31, CORIN, and TDRD9), miR-204 (FSHR, GREB1, CORIN, and TDRD9), and miR-302b-5p (CYP19A1 and TDRD9) may play crucial roles in ovarian development. These analyses provide new clues to uncover molecular mechanisms and signaling networks of ovarian development.